2023
DOI: 10.1111/odi.14621
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy upregulated immune checkpoints contribute to the development of second primary OSCC

Abstract: ObjectivesRadiation injury is common after radiotherapy for head and neck cancer. Radiotherapy can reshape the immune microenvironment and cause immunosuppression, including dysregulation of immune checkpoints (ICs). However, the relationship between oral ICs expression after radiation and the development of second primary tumors is unclear.MethodsClinical specimens of second primary oral squamous cell carcinoma after radiotherapy (s‐OSCC) and primary OSCC (p‐OSCC) were collected. The expression and prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…It has been supposed that an alteration in tissue oxygenation due radiationinduced hypoxia, hypovascularity, and hypocellularity may sustain the occurrence of a second malignancy [19]. Furthermore, it has been recently suggested that radiation-induced immune dysregulation may activate specific co-suppressor molecules called immune checkpoints (ICs); this could protect cancer cells against immune response [20]. In this light, immunotherapy could play a key role in the treatment of RISCCs, leading to clinical and pathological responses, as seen in the presented case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been supposed that an alteration in tissue oxygenation due radiationinduced hypoxia, hypovascularity, and hypocellularity may sustain the occurrence of a second malignancy [19]. Furthermore, it has been recently suggested that radiation-induced immune dysregulation may activate specific co-suppressor molecules called immune checkpoints (ICs); this could protect cancer cells against immune response [20]. In this light, immunotherapy could play a key role in the treatment of RISCCs, leading to clinical and pathological responses, as seen in the presented case.…”
Section: Discussionmentioning
confidence: 99%